Human and Mediated Communication around the World A Comprehensive Review and Analysis - de Mooij, Marieke; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2014)
This book is unique in the sense that it offers a comprehensive review and analysis of human communication and mediated communication around the world. This is one of the first attempts to do so in a systematic, comprehensive way. It challenges the assumption that Western theories of human communication and mass communication have universal applicability. It surveys the applicability of mass communication theories to other than Western cultures. The book explains the influence of culture on all forms of communication behavior, be it personal, mediated or mass communication. It presents communication theories from around the world, incorporating a vast body of literature from Europe, Asia, Africa and Latin America. This updated information on important international perspectives that includes both interpersonal and mediated communication is presently not readily available in other sources. The book offers an integrated approach to understanding the working of electronic means of communication that are hybrid media combining human and mediated communication. These new media that are often presented as universal are even more culture-bound than the traditional media.
Preface- Chapter 1. Communication -- Chapter 2. Orality and Literacy -- Chapter 3. European and American Communication Theories -- Chapter 4. Asian Communication -- Chapter 5. African and West-Asian Communication -- Chapter 6. Culture and Cultural Dimensions -- Chapter 7. Culture, Self and Communication -- Chapter 8. Media Behavior and Culture -- Chapter 9. Communication Products and Culture -- Chapter 10. Mass Media, Journalism, Society and Culture -- Chapter 11. Theories of Mass Communication and Media Effects across Cultures -- Chapter 12. Behavior Change Communication -- Literature.
Keywords: Social sciences; Mass media; Applied psychology; Social Sciences; Communication Studies; Media Management; Cross Cultural Psychology; Communication Studies